La influencia de los eventos deportivos como motivación en la elección de un destino turístico y como motor de desarrollo del mismo - Blanco Gregory, Rocío (Eracle. Journal of Sport and Social Sciences, 2018)
In this descriptive article, we present the development experienced in recent years of the tourism sector in Extremadura (Spain), focusing on tourism related to sport and adventure, classifying the different types of sports practiced in the autonomous community, how sport has evolved in general over the years and, finally, the different companies dedicated to the conjugation of sporting events with tourism, which have boomed so much today. Sports tourism encompasses all activities that relate to sports in general. The main activities that can be highlighted are tourist trips to a specific destination that has been chosen, because important sporting events have been developed or the possibility of practicing sports in the same environment. The influence exercised by the media together with public institutions on the healthy aspects of sports, causes society to consider itself as another reason to travel to a certain destination and to experience what is publicized in these media. This entails an increase in the number of visitors to the destination in particular favoring, in turn, a remarkable development of economic, cultural and sports. The different business entities related to the tourism industry are using the great power of attraction of these sporting events, increasingly, as a strategy to promote a region or a country as tourist destinations.